Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2015)
A dataset containing 135976 species occurrences available in GBIF matching the query: { "and" : [ "Country is Mexico", "Geometry POLYGON((-97.728881 21.932854,-98.558349 21.509296,-98.679199 21.176728,-99.080200 21.186972,-99.398803 21.079374,-99.525146 20.632784,-99.876708 20.262197,-100.151367 19.875225,-100.255737 19.425153,-100.349121 19.228176,-99.662475 19.305959,-98.618774 19.885557,-97.404785 20.024967,-97.229003 20.720153,-97.470703 21.253541,-97.728881 21.932854))" ] } The dataset includes 135976 records from 320 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0000317-150922153815467/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences